Acupuncture and Dry Needling in the Reduction of Peripheral Acute Fatigue Induced in the Biceps Braquii: Protocol for a Single-blinded Randomized Controlled Clinical Trial - Gabriel Barreto Antonino; Ana Paula de Lima Ferreira; Eduardo José Nepomuceno Montenegro; Alberto Galvão de Moura Filho; Arthur Felipe Freire da Silva; Maria das Graças Rodrigues de Araújo (Medical Association of Pharmacopuncture Institute, 2020)
The present study aims to propose a protocol to verify the efficacy and acute effects of traditional Chinese acupuncture, dry needling, and the rest in peripheral acute fatigue (PAF) induced by intermittent isometric contractions of the nondominant biceps brachii (BB) of nonphysically active men in a randomized, single-blind clinical trial assessed with surface electromyography, contraction time in seconds, infrared thermal imaging, and visual analog scale applied to the PAF. These instruments will evaluate the median frequency, endurance time, temperature (°C), and perceived fatigue in BB of the volunteers. The measurements will be collected in four moments (Test 0, 01, 02, and 03) divided between the beginning and the end of two sets of exercises (Exercises 01 and 02) of intermittent isometric contractions. Trial identifier: NCT03448120 in www.clinicaltrials.gov.